A review of self-organising 2, 5- and 2, 4-disubstituted 1, 3-thiazole-containing materials: synthesis, mechanisms and tactics. Issue 12 (21st October 2017) - Seed, Alexander J.; Sampson, Paul
ABSTRACT: 2, 5- and 2, 4-disubstituted 1, 3-thiazoles have been incorporated as core units in thermotropic liquid crystalline materials. However, synthetic approaches to these systems have been somewhat limited, and this is reflected in the relatively few reports of these mesogenic systems. This paper highlights both recent and well-established synthetic approaches to these systems using ring closure (Gabriel- and Hantzsch-type approaches) methodology and modifications of an intact 1, 3-thiazole ring. The scope and limitations of each of these approaches are discussed. Graphical Abstract: